Edukasi Kesehatan pada Orang Tua Sebagai Upaya Pencegahan Pneumonia pada Anak Balita di Kelurahan Balocci Baru - Tiala, Nur Hijrah; Latif, Aulia Insani; La Masahuddin (PT.Mantaya Idea Batara, 2023)
Pneumonia is a form of acute respiratory infection that attacks the lungs and is the highest cause of death in children in the world. Parents play a major role in children's health as the nation's next generation who must receive protection and their right to health, including avoiding pneumonia. The low knowledge of parents in the Balocci Baru sub-district, Balocci sub-district, Pangkep Regency is a partner problem so that it is necessary to provide health education about pneumonia to increase community information and knowledge in preventing pneumonia in toddlers. The method of dedication is by Lectures/counseling, Discussions and questions and answers. The results of the service showed that parents' curiosity regarding pneumonia was very high, seen from their enthusiasm in asking. After counseling the parents experienced an increase in knowledge about the efforts that must be made in preventing pneumonia in children.